Celebrating Multiculturalism in School Education: Parents’ Perspectives - Chettry, Geeta (Nepal Journal of Multidisciplinary Research, 2023)
Inclusion is progressively becoming a fundamental aspect of societal norms. Multicultural education is an educational approach that aims to integrate diversity into the learning process. The objective of this educational approach is to mitigate biases and stereotypes associated with other cultures and ethnicities. Nepal is a diverse nation, including several cultures, languages, and ethnic groups within a compact geographical region. In an increasingly globalized society, the implementation of multicultural education is imperative, but it presents some difficulties. This study examines the role of parents in implementing multicultural education in a school context by exploring their viewpoints and understanding of the topic.